Colouristic Vocabulary in Yurii Fedkovych’s Poetry (Linguostylistic Studies, 2016)
The article provides a complex analysis of colouristic vocabulary in poetic idiolect of Yuri Fedkovych. The author proves that colouristic vocabulary used in lyric and lyric-epic works by Fedkovych is one of the peculiar features of the individual style of the writer from Bukovyna in the second half of the nineteenth century. The lexical meaning, traditionality and originality in the use of colouristic vocabulary by the writer, his personal colour preferences are analyzed. The stylistic features of this type of language, its role in the creation of artistic images, representation of the inner world of the characters are investigated. The article sheds the light on the establishment of the Ukrainian language on the territory of Bukovyna in the times of Austrian Empire expansion in the second half of the nineteenth century.Key words: verbal picture of the world, individual style, semantics, stylistic role, speech activity, images, associations. References